Gender Wage Inequality and Economic Growth: Is there Really a Puzzle? - Thomas Schober; Rudolf Winter-Ebmer (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2009)
Seguino (2000) shows that gender wage discrimination in export-oriented semi-industrialized countries might be fostering investment and growth in general. While the original analysis does not have internationally comparable wage discrimination data, we replicate the analysis using data from a meta-study on gender wage discrimination and do not find any evidence that more discrimination might further economic growth on the contrary: if anything the impact of gender inequality is negative for growth. Standing up for more gender equality also in terms of wages is good for equity considerations and at least not negative for growth.
Keywords: 330